Outcome of immunotherapy in adrenocortical carcinoma: a retrospective cohort study - Remde, Hanna; Schmidt-Pennington, Laura; Reuter, Miriam; Landwehr, Laura-Sophie; Jensen, Marie; Lahner, Harald; Kimpel, Otilia; Altieri, Barbara; Laubner, Katharina; Schreiner, Jochen; Bojunga, Joerg; Kircher, Stefan; et al. (European journal of endocrinology, 2023)
Clinical trials with immune checkpoint inhibitors (ICI) in adrenocortical carcinoma (ACC) have yielded contradictory results. We aimed to evaluate treatment response and safety of ICI in ACC in a real-life setting.Retrospective cohort study of 54 patients with advanced ACC receiving ICI as compassionate use at 6 German reference centres between 2016 and 2022.Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and treatment-related adverse events (TRAE) were assessed.In 52 patients surviving at least 4 weeks after initiation of ICI, ORR was 13.5% (6-26) and DCR was 24% (16-41). PFS was 3.0 months (95% CI, 2.3-3.7). In all patients, median OS was 10.4 months (3.8-17). 17 TRAE occurred in 15 patients, which was associated with a longer PFS of 5.5 (1.9-9.2) vs 2.5 (2.0-3.0) months (HR 0.29, 95% CI, 0.13-0.66, P = 0.001) and OS of 28.2 (9.5-46.8) vs 7.0 (4.1-10.2) months (HR 0.34, 95% CI, 0.12-0.93). Positive tissue staining for programmed cell death ligand 1 (PD-L1) was associated with a longer PFS of 3.2 (2.6-3.8) vs 2.3 (1.6-3.0, P < 0.05) months. Adjusted for concomitant mitotane use, treatment with nivolumab was associated with lower risk of progression (HR 0.36, 0.15-0.90) and death (HR 0.20, 0.06-0.72) compared to pembrolizumab.In the real-life setting, we observe a response comparable to other second-line therapies and an acceptable safety profile in ACC patients receiving different ICI. The relevance of PD-L1 as a marker of response and the potentially more favourable outcome in nivolumab-treated patients require confirmation.
Veröffentlicht: 01. Juni 2023
Gesehen am 27.07.2023